Deep Web Data Scraper: Search Engine - Nain, Sneh; Lall, Bhumika (International Journal of Computer Sciences and Engineering, 2014)
World Wide Web is growing every day and people generally depend on search engine to explore the web. Searching on the web today can be compared to dragging a net across the surface of the ocean. Traditional search engine extracts data from the small portion of the web whereas the large portions of the web are hidden behind search forms, in searchable structured and unstructured database. Deep web contains the high quality content and large coverage area. A lot of research has been carried out in this area to make the hidden data float on the surface of web. In this paper, we discussed the problem faced by users in scraping the information from the deep web and also discussed the solution of these problems by using our new approach